2004
DOI: 10.1038/sj.onc.1208080
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between Src and integrins in normal and tumor biology

Abstract: Src family nonreceptor protein tyrosine kinases transduce signals that control normal cellular processes such as cell proliferation, adhesion and motility. Normally, cellular Src is held in an inactive state, but in several cancer types, abnormal events lead to elevated kinase activity of the protein and cause pleiotropic cellular responses inducing transformation and metastasis. A prerequisite of the ability of a cancer cell to undergo metastasis into distant tissues is to penetrate surrounding extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
424
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(447 citation statements)
references
References 237 publications
(275 reference statements)
22
424
1
Order By: Relevance
“…However, orthovanadate pretreatment did not reverse the TIMP-2 mediated increase in FAK phosphorylation at Tyr397, suggesting that phosphorylation at this site is independent of protein tyrosine phosphatase activity. Studies showed that phosphorylated Tyr-397 residue of FAK serves as a binding site for Src, which in turn promotes Src kinase activation (Playford and Schaller, 2004). Our immunoprecipitation using anti-Src antibody, however, showed no significant changes in the association of FAK-Src upon TIMP-2 treatment (data not shown), suggesting that TIMP-2 may affect Src kinase activity independently of FAK.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…However, orthovanadate pretreatment did not reverse the TIMP-2 mediated increase in FAK phosphorylation at Tyr397, suggesting that phosphorylation at this site is independent of protein tyrosine phosphatase activity. Studies showed that phosphorylated Tyr-397 residue of FAK serves as a binding site for Src, which in turn promotes Src kinase activation (Playford and Schaller, 2004). Our immunoprecipitation using anti-Src antibody, however, showed no significant changes in the association of FAK-Src upon TIMP-2 treatment (data not shown), suggesting that TIMP-2 may affect Src kinase activity independently of FAK.…”
mentioning
confidence: 58%
“…Several signaling molecules that localize at focal adhesions include focal adhesion kinase (FAK), Src tyrosine kinase, and paxillin. It has been demonstrated that upon integrin stimulation, tyrosine phosphorylation of FAK and Src kinase is enhanced (Parsons, 2003;Playford and Schaller, 2004). As TIMP-2 signaling requires its selective interaction with integrin a3b1 (Seo et al, 2003;Oh et al, 2004;Perez-Martinez and Jaworski, 2005), we sought to determine the effects of TIMP-2 on the phosphorylation status of FAK and Src.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moesin is a member of the ERM (Ezrin/ Radixin/Moesin) family of proteins which have been shown to interact with src in adhesion-mediated signaling [34,35]. As stated above YAP-1 directly interacts with src and another SFK proto-oncogene yes, possibly in the tight junction and adherens pathways [21,36].…”
Section: Discussionmentioning
confidence: 99%
“…While in vitro studies have shown that Src can regulate many different molecules including intracellular signaling intermediates, integrins, matrix metalloproteases, and ECM proteins, the specific role of Src in vivo is poorly understood [67][68][69][70][71][72][73][74][75][76]. Based on knockout studies, it is known that other Src-related family kinases can compensate for the absence of Src particularly during development.…”
Section: Discussionmentioning
confidence: 99%